Manufacturing method of superabsorbent resin
By employing a cross-polymerization and dual-stage surface crosslinking process with specific agents, the method enhances the surface crosslinking strength of superabsorbent resins, maintaining water absorption capacity under pressure despite anti-caking treatments.
Patent Information
- Application Number
- JP2022546525
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-27
- Filing Date
- 2021-10-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-10-28
AI Technical Summary
Superabsorbent resins experience a decrease in water absorption capacity under pressure due to increased surface friction caused by anti-caking agents, which hinder swelling, particularly in areas with high humidity.
A method involving the cross-polymerization of water-soluble ethylenically unsaturated monomers with a polymerization initiator and internal cross-linking agent, followed by primary and secondary surface crosslinking using agents with different molecular weights to enhance surface crosslinking strength, ensuring pressurized water absorption capacity.
The method maintains or minimizes the decrease in water absorption capacity under pressure even after anti-caking treatment, improving the physical properties of superabsorbent resins.
Smart Images

Figure 0007612164000001 
Figure 0007612164000002
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0142300 filed on October 29, 2020, and Korean Patent Application No. 10-2021-0144931 filed on October 27, 2021, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a method for producing a highly water-absorbent resin. [Background technology]
[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that can absorb 500 to 1,000 times its own weight in water, and is given different names by different developers, such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). Such super absorbent polymers were first put to practical use as sanitary products, and are now widely used as soil repair agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution field, and materials for wet wipes, and are mainly used in the field of sanitary products such as diapers and sanitary belts.
[0004] As the global trend shifts to thinner diapers, the proportion of pulp constituting the absorbent core of diapers is decreasing and the proportion of superabsorbent polymer is increasing.
[0005] As the proportion of superabsorbent polymer in diapers increases, the physical properties of SAP become more important, especially the absorbency and permeability under pressure, which affect the rewet and water absorption speed of the diaper under pressure.
[0006] Since superabsorbent resin is a polymer with the property of absorbing water, caking can occur in areas with high humidity, and to prevent this, an anti-caking agent is added. Anti-caking agents are generally inorganic substances that do not absorb water. Inorganic substances are also used as additives to improve permeability and prevent blocking between SAP particles.
[0007] However, the inorganic matter increases the surface friction during the swelling process of the superabsorbent resin, thereby hindering the swelling under pressure conditions, resulting in a decrease in the water absorption capacity under pressure. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a superabsorbent resin which exhibits little or no decrease in water absorption capacity under pressure even after treatment with an anti-caking agent by increasing the surface crosslinking strength of the superabsorbent resin. [Means for solving the problem]
[0009] According to one embodiment of the present invention, there is provided a method for producing a superabsorbent resin, the method including: cross-linking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of a polymerization initiator and an internal cross-linking agent to form a hydrogel polymer containing a cross-linked polymer of the water-soluble ethylenically unsaturated monomer; drying, pulverizing, and classifying the hydrogel polymer to obtain a base resin powder; primarily surface-cross-linking the base resin powder while raising the temperature to a first temperature in the presence of a first surface cross-linking agent; and secondary surface-cross-linking the primarily surface-cross-linked base resin powder at a second temperature in the presence of a second surface cross-linking agent to form superabsorbent resin particles; wherein the first temperature is 180° C. or higher, the second temperature is 120° C. to 150° C., and the second surface cross-linking agent has a weight average molecular weight higher than that of the first surface cross-linking agent and contains an epoxy compound capable of forming a covalent bond at the second temperature.
[0010] According to another embodiment of the present invention, there is provided a superabsorbent resin comprising: a base resin powder produced by the above-mentioned production method, the base resin powder comprising a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group; and a surface crosslinked layer located on the base resin powder; the surface crosslinked layer comprises a first crosslinked polymer in which a part of the crosslinked polymer has been additionally crosslinked via a first surface crosslinking agent; and a second crosslinked polymer in which the remainder of the crosslinked polymer has been additionally crosslinked via a second surface crosslinking agent, the second surface crosslinking agent having a weight average molecular weight larger than that of the first surface crosslinking agent and comprising an epoxy compound capable of forming a covalent bond at 120 to 150°C.
[0011] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.
[0012] The present invention can be modified in various ways and can have various forms, and the following detailed description will be given of specific embodiments by way of example, but it should be understood that the present invention is not limited to the specific disclosed embodiments, but includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0013] The term "polymer" or "polymeric polymer" used in the present specification means a state in which a water-soluble ethylenically unsaturated monomer is polymerized, and may include any range of water content or particle size. Among the above polymers, a polymer in a state after polymerization and before drying and having a water content of about 40% by weight or more may be called a hydrogel polymer.
[0014] The base resin means a particulate resin or powder obtained by drying and pulverizing the hydrogel polymer, which has not undergone additional steps such as surface crosslinking, regranulation into fine powder, redrying, repulverization, or reclassification.
[0015] Furthermore, depending on the context, the term "super absorbent polymer" refers to the polymer or base resin itself, or is used to encompass all of the polymers or base resins that have been subjected to additional processes, such as surface crosslinking, fine powder regranulation, drying, pulverization, classification, and the like, to be in a state suitable for commercialization.
[0016] Hereinafter, a method for producing a superabsorbent polymer according to a specific embodiment of the present invention and the superabsorbent polymer produced thereby will be described in more detail.
[0017] Specifically, the method for producing a superabsorbent resin according to one embodiment of the present invention includes the steps of: A step (step 1) of cross-polymerizing a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of a polymerization initiator and an internal cross-linking agent to form a hydrogel polymer containing a cross-linked polymer of the water-soluble ethylenically unsaturated monomer; drying, grinding, and classifying the hydrogel polymer to obtain a base resin powder (Step 2); a step of subjecting the base resin powder to a first surface crosslinking while increasing the temperature to a first temperature in the presence of a first surface crosslinking agent (step 3); and Step 4: secondarily surface-crosslinking the first surface-crosslinked base resin powder at a second temperature in the presence of a second surface-crosslinking agent to form superabsorbent resin particles; The first temperature is 180° C. or more, and the second temperature is 120 to 150° C., The second surface cross-linking agent has a weight average molecular weight greater than that of the first surface cross-linking agent and includes an epoxy-based compound capable of forming a covalent bond at the second temperature.
[0018] In general, the larger the surface area of a superabsorbent resin, the faster the water absorption rate. However, if the surface area of a superabsorbent resin is large due to limitations in production equipment, it is difficult to sufficiently apply a surface cross-linking agent, resulting in a problem that the pressurized water absorption capacity of the final superabsorbent resin is greatly reduced.
[0019] In contrast, in the present invention, when producing a superabsorbent resin, a surface crosslinking agent having a small weight average molecular weight is subjected to a first surface crosslinking reaction at a high temperature so that the surface crosslinking agent penetrates deep into the surface of the superabsorbent resin, thereby securing the pressurization characteristics of the superabsorbent resin, and then a second surface crosslinking reaction is performed using an epoxy-based surface crosslinking agent having a larger weight average molecular weight than that in the first surface crosslinking reaction and capable of forming a covalent bond in an optimal temperature range, thereby preventing or reducing the decrease in the pressurized water absorption capacity even after anti-caking treatment. In addition, the above production method is particularly effective for producing a superabsorbent resin with a large surface area and high water absorption rate.
[0020] In addition, even in the conventional manufacturing method in which only the first surface crosslinking is performed, the decrease in water absorption capacity of the superabsorbent resin under pressure due to the anti-caking treatment can be reduced, but in this case, the surface crosslinking reaction must be performed many times, which causes a problem of a large decrease in water retention capacity (CRC). In contrast, in the present invention, the surface that remains unreacted after the first surface crosslinking is second surface crosslinked using a surface crosslinking agent that has a large Mw compared to the first surface crosslinking agent and a fast reaction rate even at low temperatures, thereby greatly reducing the decrease in water absorption capacity under pressure to less than 5% and simultaneously minimizing the loss of water retention capacity.
[0021] In addition, by using a surface crosslinking agent with a fast reaction rate at low temperature during the second surface crosslinking, the second surface crosslinking process can be performed by the residual heat from the first surface crosslinking during the cooling process without a separate heating process after the first surface crosslinking process, which is performed at a high temperature of about 180℃.
[0022] Hereinafter, each step of the method for producing a superabsorbent resin according to an embodiment of the present invention will be described in detail.
[0023] (Stage 1) In the method according to one embodiment of the invention, step 1 is to prepare a hydrogel polymer.
[0024] Specifically, step 1 can be carried out by mixing a water-soluble ethylenically unsaturated monomer having an acidic group and at least a portion of the acidic group being neutralized, a polymerization initiator, and an internal crosslinking agent to prepare a monomer composition, and polymerizing the monomer composition. For example, the monomer composition can be prepared by adding a polymerization initiator and an internal crosslinking agent to a neutralization solution obtained by neutralizing a water-soluble ethylenically unsaturated monomer having an acidic group, and mixing the neutralization solution.
[0025] The water-soluble ethylenically unsaturated monomer in which at least a part of the acidic groups has been neutralized can be produced by neutralizing the acidic groups of the water-soluble ethylenically unsaturated monomer with a neutralizing agent.
[0026] The water-soluble ethylenically unsaturated monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following formula 1:
[0027] [Chemical formula 1] R1-COOM
[0028] In the above chemical formula 1, R1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0029] Preferably, the monomer may be one or more selected from the group consisting of (meth)acrylic acid, and monovalent (alkali) metal salts, divalent metal salts, ammonium salts and organic amine salts of these acids.
[0030] In this way, when (meth)acrylic acid and / or its salt is used as the water-soluble ethylenically unsaturated monomer, it is advantageous to obtain a superabsorbent resin with improved water absorption. Other examples of the monomer that can be used include maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate, (N,N)-dimethylaminopropyl (meth)acrylamide, etc.
[0031] In addition, the concentration of the water-soluble ethylenically unsaturated monomer in the monomer composition can be appropriately adjusted in consideration of the polymerization time and reaction conditions, and may be preferably 20 to 90% by weight, or 40 to 65% by weight. This concentration range may be advantageous for adjusting the pulverization efficiency when pulverizing the polymer described below while eliminating the need to remove unreacted monomers after polymerization using the gel effect phenomenon that appears in the polymerization reaction of a high concentration aqueous solution. However, if the concentration of the monomer is excessively decreased, the yield of the superabsorbent resin may be decreased. Conversely, if the concentration of the monomer is excessively increased, a process problem may occur, such as a part of the monomer being precipitated or the pulverization efficiency being reduced when the polymerized hydrogel polymer is pulverized, and the physical properties of the superabsorbent resin may be reduced.
[0032] As the neutralizing agent, a basic substance capable of neutralizing an acidic group, such as sodium hydroxide (or caustic soda), potassium hydroxide, or ammonium hydroxide, can be used.
[0033] The amount of the neutralizing agent and the neutralization reaction process are not particularly limited, and can be performed so that the neutralization degree of the water-soluble ethylenically unsaturated monomer, which refers to the degree to which the acidic groups contained in the water-soluble ethylenically unsaturated monomer are neutralized by the neutralizing agent, is 50 to 90 mol%, or 60 to 85 mol%, or 65 to 85 mol%, or 70 to 80 mol%. The range of the neutralization degree can vary depending on the final physical properties, but if the neutralization degree is too high, the neutralized monomer may precipitate and polymerization may not proceed smoothly, and conversely, if the neutralization degree is too low, the absorbency of the polymer may be greatly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.
[0034] Meanwhile, in the monomer composition, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation such as UV irradiation, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may be additionally included.
[0035] The photopolymerization initiator can be used without any limitation on its composition as long as it is a compound capable of forming radicals by light such as ultraviolet light. As the photopolymerization initiator, for example, one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkylketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone can be used. Meanwhile, specific examples of acylphosphine include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate. A wide variety of photopolymerization initiators are described in detail in "UV Coatings: Basics, Recent Developments and New Applications" by Reinhold Schwalm (Elsevier, 2007), p. 115, and are not limited to the above-mentioned examples.
[0036] The photopolymerization initiator can be used in an amount of 0.001 to 5 parts by weight, or 0.005 to 4.5 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.
[0037] The thermal polymerization initiator may be at least one selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitril, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. A wide variety of thermal polymerization initiators are well described in Odian's book 'Principle of Polymerization' (Wiley, 1981), p. 203, and are not limited to the above examples.
[0038] The thermal polymerization initiator can be used in an amount of 0.01 to 5 parts by weight, or 0.1 to 4 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the concentration of the thermal polymerization initiator is too low, the polymerization rate may be slowed down, and a large amount of residual monomer may be extracted into the final product. If the concentration of the thermal polymerization initiator is too high, the polymer chain forming the network of the superabsorbent resin becomes shorter, increasing the content of water-soluble components, which may result in a decrease in the physical properties of the resin, such as a decrease in the pressurized water absorption capacity of the superabsorbent resin.
[0039] The monomer composition also contains an internal crosslinking agent as a raw material for the highly water-absorbent resin.
[0040] As the internal crosslinking agent, any compound can be used as long as it enables the introduction of crosslinking bonds during polymerization of the water-soluble ethylenically unsaturated monomer. Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerin, and ethylene carbonate, which may be used alone or in combination of two or more. The internal crosslinking agent is not limited thereto.
[0041] Among these, when considering the improvement of the crosslinking effect and the excellent effect of improving the absorption capacity of the superabsorbent resin, it is preferable to use polyethylene glycol diacrylate, more specifically, polyethylene glycol diacrylate having a weight average molecular weight of 300 to 800 g / mol or 400 to 800 g / mol. The weight average molecular weight (Mw) of the polyethylene glycol diacrylate can be measured by gel permeation chromatography, and the specific measurement method and measurement conditions are the same as the measurement method of the weight average molecular weight (Mw) of polycarboxylic acid described later, except that the Mw value is derived using a calibration curve for a polystyrene standard specimen.
[0042] The internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the concentration of the internal crosslinking agent is too low, the water absorption speed of the resin may decrease, and the gel strength may become weak, which is not preferable. Conversely, if the concentration of the internal crosslinking agent is too high, the absorption power of the superabsorbent resin may decrease, and the absorbent may become undesirable. More specifically, the internal crosslinking agent may be included in an amount of 0.1 to 5 parts by weight, or 0.2 to 3 parts by weight.
[0043] Meanwhile, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of the base resin described below, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed without distinction between the surface and the inside, but the surface of the finally prepared superabsorbent resin has a structure crosslinked by the surface crosslinking agent and the inside has a structure crosslinked by the internal crosslinking agent through the surface crosslinking process of the base resin described below.
[0044] In addition, the monomer composition may further include one or more additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0045] The monomer composition may be prepared in the form of a solution dissolved in a solvent. Any solvent may be used as long as it can dissolve the raw materials. For example, the solvent may be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.
[0046] The solvent may be included in an amount remaining after excluding the above-mentioned components based on the total content of the monomer composition.
[0047] In addition, the solid content in the monomer composition in the solution state, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, can be appropriately adjusted in consideration of the polymerization time and reaction conditions. For example, the solid content in the monomer composition may be 10 to 80% by weight, 15 to 60% by weight, or 20 to 40% by weight. When the monomer composition has a solid content in the above range, it is advantageous for adjusting the pulverization efficiency when pulverizing the polymer described below while eliminating the need to remove unreacted monomers after polymerization using the gel effect phenomenon that appears in the polymerization reaction of a high concentration aqueous solution.
[0048] On the other hand, the method for forming the hydrogel polymer by polymerizing the above-mentioned monomer composition is not particularly limited as long as it is a commonly used polymerization method.
[0049] Specifically, the polymerization method is largely divided into thermal polymerization and photopolymerization according to the polymerization energy source, and either one of thermal polymerization and photopolymerization may be performed, or both thermal polymerization and photopolymerization may be performed. At this time, the order of performing thermal polymerization and photopolymerization is not particularly limited, and photopolymerization may be followed by thermal polymerization, or photopolymerization may be followed by thermal polymerization, or photopolymerization and thermal polymerization may be performed simultaneously. In general, thermal polymerization may be performed in a reactor having a stirring shaft such as a kneader, and photopolymerization may be performed in a reactor having a movable conveyor belt. However, the above-mentioned polymerization method is merely an example, and is not limited to the above-mentioned polymerization method.
[0050] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft or by heating the reactor as described above may be several centimeters to several millimeters in size when discharged from the reactor outlet, depending on the type of the agitator shaft installed in the reactor. Specifically, the size of the obtained hydrogel polymer varies depending on the concentration of the monomer mixture injected and the injection speed, and a hydrogel polymer having a particle size of 2 to 50 mm is usually obtained.
[0051] In addition, when photopolymerization is performed in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a sheet-like hydrogel polymer having the width of the belt. In this case, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, but it is preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. If the monomer composition is supplied so that the thickness of the sheet-like polymer is too thin, the production efficiency is low, which is undesirable, and if the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction may not occur evenly throughout the entire thickness due to the excessively thick thickness.
[0052] The water content of the hydrogel polymer obtained by this method may be 40 to 80% by weight. Meanwhile, throughout this specification, the "water content" refers to the water content relative to the total weight of the hydrogel polymer, which is the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer through infrared heating. Here, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase stage, and the water content is measured.
[0053] According to one embodiment of the present invention, the hydrogel polymer obtained above can be optionally subjected to a coarse pulverization process.
[0054] In this case, the crusher used in the coarse crushing process is not limited in structure, and specifically may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.
[0055] In this case, the coarse pulverization step can pulverize the hydrogel polymer to a particle size of about 2 to 20 mm. Coarse pulverization to a particle size of less than 2 mm is technically difficult due to the high water content of the hydrogel polymer, and the pulverized particles may aggregate with each other. On the other hand, if the particle size exceeds 20 mm, the efficiency increase effect of the subsequent drying step may be minimal.
[0056] (Stage 2) Next, in step 2, the hydrogel polymer prepared in step 1 is dried, crushed and classified to prepare a base resin.
[0057] The drying process for the hydrogel polymer can be carried out at 50 to 250°C. If the drying temperature is less than 50°C, the drying time is too long, which may cause the properties of the finally formed superabsorbent polymer to deteriorate, and if the drying temperature exceeds 250°C, only the polymer surface is dried excessively, which may cause fine powder to be generated in the subsequent pulverization process, which may cause the properties of the finally formed superabsorbent polymer to deteriorate. More preferably, the drying can be carried out at a temperature of 150 to 200°C, and even more preferably at a temperature of 160 to 190°C. Meanwhile, the drying time can be carried out for 20 minutes to 15 hours in consideration of process efficiency, but is not limited thereto.
[0058] In addition, the drying method can be selected and used without any limitation in its configuration as long as it is a method commonly used for drying a hydrogel polymer. Specifically, the drying step can be performed by a method such as hot air supply, infrared radiation, microwave radiation, or ultraviolet radiation.
[0059] The moisture content of the dried polymer after the drying step may be 5% by weight or less, more specifically, 0.1 to 3% by weight. If the moisture content of the dried polymer exceeds 5% by weight, a non-dried resin can be obtained.
[0060] The dried polymer is then ground and classified.
[0061] The polymer powder obtained after the pulverization may have a particle size of 150 to 850 μm. The pulverizer used for pulverizing to such a particle size may be, but is not limited to, a ball mill, a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill.
[0062] In order to control the physical properties of the superabsorbent resin powder that is the final product after the pulverization step, the polymer powder obtained after pulverization may be classified according to particle size. Preferably, the polymer having a particle size of 150 to 850 μm is classified, and only the polymer powder having such a particle size may be processed into a product through the surface crosslinking reaction step described below.
[0063] The base resin powder obtained through the above process is suitably manufactured and provided to have a particle size of 150 to 850 μm. More specifically, at least 95% by weight of the base resin powder may have a particle size of 150 to 850 μm, and fine powder having a particle size of less than 150 μm may be less than 3% by weight. By controlling the particle size distribution of the base resin powder within a preferred range, the finally manufactured superabsorbent resin can already exhibit the above-mentioned physical properties better.
[0064] Unless otherwise specified in this specification, the "particle size or particle size" may be measured by a standard sieve analysis method or a laser diffraction method, preferably by a standard sieve analysis method, and the "average particle size or weight average particle size" may mean a particle size D50 that is 50% by weight in a particle size distribution curve obtained by a laser diffraction method.
[0065] Meanwhile, in this specification, fine particles having a particle size below a certain particle size, i.e., less than about 150 μm, are referred to as base resin fine powder, superabsorbent polymer fine powder, SAP fine powder, or fine powder, and particles with a particle size of 150 to 850 μm are referred to as normal particles.
[0066] The fine powder may be generated during the polymerization process, drying process, or pulverization of the dried polymer, and if the fine powder is present in the final product, it may be difficult to handle and may cause gel blocking, etc., which may result in reduced physical properties. Therefore, it is preferable to remove the fine powder so that it is not included in the final resin product, or to re-granulate the fine powder to make it into normal particles.
[0067] For example, the fine powder may undergo a regranulation process to aggregate it to the normal particle size. In the regranulation process, a regranulation process is generally performed in which the fine powder particles are aggregated in a wet state to increase the aggregation strength. At this time, the higher the moisture content of the fine powder, the higher the aggregation strength of the fine powder, but excessively large lumps of the regranulated material may be formed during the regranulation process, causing problems during operation. If the moisture content is low, the regranulation process is easy, but the aggregation strength is low and the regranulated material is often crushed into fine powder again after regranulation (re-pulverization). In addition, the regranulated fine powder thus obtained may have lower physical properties such as water retention capacity (CRC) and absorbent under pressure (AUL) than normal particles, resulting in a decrease in the quality of the superabsorbent resin.
[0068] In contrast, the method according to an embodiment of the present invention may further include a step of adding water and additives to the fine powder, regranulating the fine powder to prepare a fine powder regranulated product, and then mixing the regranulated product with the base resin powder.
[0069] When producing the fine powder regranulated product, the fine powder, additives, and water can be mixed by stirring at a speed of about 10 to about 2000 rpm, about 100 to about 1000 rpm, or about 500 to about 800 rpm using a mixing device or mixer capable of applying shear force.
[0070] After the mixing, a drying process may be performed. Specifically, the drying process may be performed at about 120 to about 220° C. to form a fine regranulated product having improved cohesive strength through covalent bonds, and the moisture content of the fine regranulated product may be adjusted to about 1 to about 2% by weight within a suitable time.
[0071] In addition, the drying process can be performed using a conventional drying device, and according to one embodiment of the invention, it can be performed using a hot air dryer, a paddle type dryer, a forced circulation dryer, or the like. In addition, there is no limitation on the configuration of the temperature increasing means for drying during the drying process. Specifically, it can be heated directly by supplying a heat medium or by electricity, but the present invention is not limited to the above examples. Specifically, usable heat sources include steam, electricity, ultraviolet rays, infrared rays, and the like, and heated thermal fluids, etc. can also be used.
[0072] The fine regranulated material obtained through the step of preparing the fine regranulated material has high cohesive strength and has a low rate of being re-crushed into fine powder after being pulverized, i.e., a low rate of being re-pulverized.
[0073] The fine regranulated material can be pulverized so that the particle size of the fine regranulated material is about 150 to about 850 μm. Specific examples of the pulverizer used for pulverizing the fine regranulated material to such a particle size include a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, and a jog mill, but the present invention is not limited to the above examples.
[0074] After the pulverization step, in order to control the physical properties of the superabsorbent resin powder to be manufactured as a final product, the regranulated powder obtained after pulverization is generally classified according to particle size. Preferably, the regranulated powder may be classified into fine regranulated powder having a particle size of 150 μm or less (hereinafter referred to as "refined powder") and normal regranulated powder having a particle size of more than 150 μm and 850 μm or less.
[0075] The regranulated normal particles can be mixed with the previously prepared base resin powder and then manufactured into a superabsorbent resin through a subsequent process. In this case, the regranulated normal particles can be mixed in an amount of 1 to 40 parts by weight with respect to 100 parts by weight of the base resin powder.
[0076] (Stage 3) Next, in step 3, the base resin powder or the base resin powder containing the regranulated normal particles is primarily surface-crosslinked while heating to a first temperature in the presence of a first surface crosslinking agent.
[0077] The surface cross-linking is a step of increasing the cross-linking density near the surface of the superabsorbent polymer particles. Generally, a surface cross-linking agent is applied to the surface of the superabsorbent polymer particles. Thus, the reaction occurs on the surface of the superabsorbent polymer particles, which improves the cross-linking property on the surface of the particles without substantially affecting the inside of the particles. Thus, the surface cross-linked superabsorbent polymer particles have a higher degree of cross-linking near the surface than the inside.
[0078] In a manufacturing method according to one embodiment of the invention, the surface cross-linking includes a first surface cross-linking step (step 3) performed by increasing the temperature from an initial temperature to a first temperature, and a second surface cross-linking step (step 4) performed at a second temperature, the second temperature being adjusted to be lower than the first temperature.
[0079] Compared with the conventional surface crosslinking process in which the surface crosslinking reaction is performed while maintaining a constant high temperature or while increasing the temperature, when the first surface crosslinking step is performed at a relatively high temperature and the second surface crosslinking step is performed at a lower temperature than the first surface crosslinking step, the second surface crosslinking agent is uniformly dispersed on the surface of the superabsorbent resin, and as a result, the surface crosslinking strength can be uniformly improved, and the anti-caking effect of the superabsorbent resin can be improved while maintaining various physical properties related to the excellent absorption performance of the superabsorbent resin.
[0080] Specifically, the first temperature in the first surface crosslinking step may be 180°C or higher, more specifically 180-200°C, and the second temperature in the second surface crosslinking reaction may be 120-150°C. By carrying out the first surface crosslinking reaction at a high temperature of 180°C or higher as described above, the surface of the base resin is sufficiently crosslinked, and excellent water absorption capacity under pressure can be exhibited. If the first temperature is less than 180°C, the first surface crosslinking reaction does not occur sufficiently, making it difficult to ensure surface crosslinking strength, and as a result, the 0.9 AUL drop rate after anti-caking treatment may increase. In addition, if the second temperature exceeds 150°C outside the above temperature range, the solvent evaporates quickly before the second surface crosslinking agent is sufficiently mixed with the first surface crosslinked base resin, and is locally absorbed into the first surface crosslinked base resin. As a result, the surface reaction is carried out under conditions where the second surface crosslinking agent is locally applied, reducing the effect of the second surface crosslinking, and the absorption performance, especially the CRC, of the superabsorbent resin produced is reduced. In addition, if the second temperature is less than 120° C., the secondary surface cross-linking reaction does not proceed sufficiently, resulting in a large increase in the 0.9 AUL drop rate after the anti-caking treatment of the superabsorbent resin. More specifically, the first temperature may be 180° C. or more, or 185° C. or more, and 200° C. or less, or 195° C. or less, or 190° C. or less, and the second temperature may be 120° C. or more, or 125° C. or more, or 130° C. or more, and 150° C. or less, or 145° C. or less, or 140° C. or less.
[0081] In addition, in the manufacturing method according to one embodiment of the present invention, the first surface crosslinking agent for the first surface crosslinking can be a compound that can react with a functional group of the polymer and has a weight average molecular weight smaller than that of the second surface crosslinking agent. When the first surface crosslinking agent having a weight average molecular weight smaller than that of the second surface crosslinking agent is subjected to a surface crosslinking reaction at a high temperature, the first surface crosslinking agent penetrates deep into the surface of the superabsorbent resin, thereby ensuring the pressurization characteristics of the superabsorbent resin.
[0082] Specifically, as the first surface crosslinking agent, a compound having a weight average molecular weight such that the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent satisfies 1.8 or more, or 1.8 to 15 can be used.
[0083] More specifically, the first surface crosslinking agent may have a weight average molecular weight of 50 to 200 g / mol, more specifically, the weight average molecular weight may be 50 g / mol or more, or 60 g / mol or more, or 70 g / mol or more, or 75 g / mol or more, and 200 g / mol or less, or 150 g / mol or less, or 120 g / mol or less, or 100 g / mol or less, or 90 g / mol or less, or 85 g / mol or less. The weight average molecular weight (Mw) of the first surface crosslinking agent can be measured using gel permeation chromatography, and the specific measurement method and measurement conditions are the same as the measurement method of the weight average molecular weight (Mw) of polycarboxylic acid described later, except that the value of Mw is derived using a calibration curve for a polystyrene standard specimen.
[0084] Moreover, the first surface cross-linking agent is a compound different from the second surface cross-linking agent.
[0085] As an example, the first surface crosslinking agent may be a non-epoxy compound, and the second surface crosslinking agent may be an epoxy compound having a weight average molecular weight larger than that of the first surface crosslinking agent and capable of forming a covalent bond at 120 to 150°C.
[0086] Specifically, the first surface cross-linking agent may be a non-epoxy compound capable of forming a covalent bond at a temperature of 180° C. or higher. More specifically, the first surface cross-linking agent may be a polyhydric alcohol compound or an alkylene carbonate compound, and any one or a mixture of two or more of these may be used.
[0087] Specific examples of the polyhydric alcohol compound include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol, and any one or a mixture of two or more of these can be used.
[0088] Specific examples of the alkylene carbonate compound include alkylene carbonates having 2 to 6 carbon atoms, such as ethylene carbonate and propylene carbonate, and any one or a mixture of two or more of these can be used.
[0089] More specifically, the first surface crosslinking agent may be one or more of polyhydric alcohol compounds or alkylene carbonate compounds satisfying the molecular weight range condition, specifically, the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent is 1.8 or more, or 1.8 to 15. In addition, the first surface crosslinking agent may be one or more of polyhydric alcohol compounds or alkylene carbonate compounds having a weight average molecular weight of 50 to 200 g / mol.
[0090] Such a first surface crosslinking agent can be used in an amount of 0.01 to 5 parts by weight relative to 100 parts by weight of the base resin. If the amount of the first surface crosslinking agent used is less than 0.01 parts by weight, the effect of using the first surface crosslinking agent is small, and as a result, it is difficult to ensure the pressurization characteristics of the superabsorbent resin. If the amount used exceeds 5 parts by weight, excessive surface crosslinking occurs, and various physical properties of the superabsorbent resin, especially the absorption capacity, may be excessively reduced. More specifically, the first surface crosslinking agent can be used in an amount of 0.01 parts by weight or more, or 0.1 parts by weight or more, or 0.2 parts by weight or more, or 0.4 parts by weight or more, or 1 part by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 2 parts by weight or less, or 1.5 parts by weight or less relative to 100 parts by weight of the base resin.
[0091] In addition, during the primary surface cross-linking, an inorganic filler may be added together with the first surface cross-linking agent.
[0092] The inorganic filler may be silica, fumed silica, clay, alumina, silica-alumina composite, titania, zinc oxide, silicate, etc., and any one or a mixture of two or more of these may be used. The inorganic filler may be included in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the base resin powder, more specifically, 0.01 parts by weight or more, or 0.03 parts by weight or more, and 0.5 parts by weight or less, or 0.1 parts by weight or less, or 0.05 parts by weight or less.
[0093] In addition, during the first surface crosslinking, at least one additive such as an organic acid or a thickener may be selectively added.
[0094] The organic acid serves to promote the crosslinking reaction.
[0095] Specifically, the organic acid may be a carboxylic acid such as oxalic acid, acetic acid, lactic acid, citric acid, fumaric acid, tartaric acid, or maleic acid, and any one or a mixture of two or more of these may be used. Among these, oxalic acid, which has excellent miscibility with the first surface crosslinking agent, is preferably used.
[0096] The organic acid may be added in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the base resin powder, more specifically, in an amount of 0.1 part by weight or more, or 0.15 part by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 1 part by weight or less, or 0.5 parts by weight or less.
[0097] In addition, when the first surface crosslinking reaction is performed on the base resin powder in the presence of the thickener, the deterioration of physical properties can be minimized even after the pulverization process. Specifically, the thickener can be at least one selected from polysaccharides and hydroxy-containing polymers. As the polysaccharide, a gum-based thickener and a cellulose-based thickener can be used. Specific examples of the gum-based thickener include xanthan gum, gum arabic, karaya gum, tragacanth gum, ghatti gum, guar gum, locust bean gum, and psyllium seed gum, and specific examples of the cellulose-based thickener include hydroxypropylmethylcellulose, carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxymethylpropylcellulose, hydroxyethylhydroxypropylcellulose, ethylhydroxyethylcellulose, and methylhydroxypropylcellulose. On the other hand, specific examples of the hydroxy-containing polymer include polyethylene glycol and polyvinyl alcohol.
[0098] In addition, the first surface crosslinking agent can be mixed with the base resin by a conventional mixing method. For example, the first surface crosslinking agent and the base resin can be mixed in a reaction tank, the first surface crosslinking agent can be sprayed onto the base resin, or the base resin and the surface crosslinking agent can be continuously fed into a continuously operated mixer and mixed.
[0099] In addition, when the first surface crosslinking agent and the base resin are mixed, the first surface crosslinking agent and the selectively added components, specifically, inorganic additives, organic acids, thickeners, etc., can be used in a state of being dissolved or dispersed in a solvent. In this case, the solvent can be water, methanol, or a mixture thereof. When the solvent is added in this way, the first surface crosslinking agent can be uniformly dispersed in the base resin, and in this case, the uniform dispersion of the surface crosslinking agent can be induced by controlling the amount of the solvent to be added, and the aggregation phenomenon of the base resin can be prevented, and at the same time, the surface penetration depth of the crosslinking agent can be optimized. Specifically, the solvent can be used in an amount of 0.5 to 20 parts by weight, more specifically, 0.5 parts by weight or more, or 3 parts by weight or more, or 5 parts by weight or more, or 6 parts by weight or more, and 10 parts by weight or less, or 8 parts by weight or less, or 7.5 parts by weight or less, relative to 100 parts by weight of the base resin powder. In addition, when the solvent includes a mixture of water and methanol, the water and methanol may be included in a weight ratio of 1:2 to 2:1, or 1:1.2 to 1.5:1.
[0100] The first surface crosslinking step using the first surface crosslinking agent can be carried out while increasing the temperature to a first temperature, specifically 180°C or higher, more specifically 180 to 200°C, in the presence of the first surface crosslinking agent. By carrying out the first surface crosslinking reaction at such a high temperature, the surface of the base resin is sufficiently crosslinked, and excellent water absorption capacity under pressure can be exhibited. However, if the first temperature is less than 180°C, the first surface crosslinking reaction does not occur sufficiently, making it difficult to ensure the surface crosslinking strength, and as a result, the 0.9 AUL drop rate after the anti-caking treatment may increase. More specifically, the first temperature may be 180°C or higher, or 185°C or higher, and 200°C or lower, or 195°C or lower, or 190°C or lower.
[0101] The temperature raising means for the primary surface crosslinking is not particularly limited, and can be heated by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat medium to be supplied. Meanwhile, examples of the heat source to be supplied directly include heating by electricity and heating by gas, but are not limited to the above examples.
[0102] In addition, the primary surface crosslinking may further include a primary maintaining step of maintaining the first temperature after heating to the first temperature. When the maintaining step is further included, the surface crosslinking of the base resin is sufficiently uniform, and as a result, the pressurized water absorption capacity of the superabsorbent resin can be further improved.
[0103] Specifically, the first maintenance process can be performed for 50% or more, more specifically, 50% or more, 55% or more, or 60% or more, and 80% or less, 70% or less, or 65% or less of the total time for which the first surface crosslinking is performed. Here, the total time for which the first surface crosslinking is performed means the time from the time when heating is started to increase the temperature to the first temperature, specifically, from the time when the mixture of the base resin and the first surface crosslinking agent is heated to the time when the first surface crosslinking or the first surface crosslinking step is completed.
[0104] (Stage 4) Next, in step 4, the first surface cross-linked base resin powder prepared in step 3 is subjected to a second surface cross-linking reaction at a second temperature in the presence of a second surface cross-linking agent to prepare a superabsorbent resin.
[0105] As the second surface cross-linking agent, an epoxy compound having a weight average molecular weight larger than that of the first surface cross-linking agent can be used.
[0106] Specifically, the second surface crosslinking agent may have a weight average molecular weight such that the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent satisfies 1.8 or more, or 1.95 or more, or 2 or more, or 2.2 or more. However, if the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent is excessively high beyond the above range, the hydrophilicity is significantly reduced, and as a result, the absorption capacity of the superabsorbent resin may be rather reduced. Therefore, the second surface crosslinking agent may have a weight average molecular weight such that the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent satisfies 15 or less, or 10 or less, or 5 or less, or 3 or less.
[0107] When the weight average molecular weight ratio of the second surface crosslinking agent to the first surface crosslinking agent is within the above range, the penetration speed of the second surface crosslinking agent is relatively slower than that of the first surface crosslinking agent, and only the surface of the particles can be effectively crosslinked. As a result, the pressurized water absorption capacity of the superabsorbent resin can be further improved.
[0108] More specifically, the second surface crosslinking agent may have a weight average molecular weight of 100 to 600 g / mol, and more specifically, the weight average molecular weight may be 100 g / mol or more, or 120 g / mol or more, or 150 g / mol or more, or 170 g / mol or more, and 500 g / mol or less, or 300 g / mol or less, or 250 g / mol or less, or 220 g / mol or less. The weight average molecular weight (Mw) of the second surface crosslinking agent can be measured using gel permeation chromatography, and the specific measurement method and measurement conditions are the same as the measurement method of the weight average molecular weight (Mw) of polycarboxylic acid described later, except that the value of Mw is derived using a calibration curve for a polystyrene standard specimen.
[0109] More specifically, in the above-mentioned preparation method, the first surface crosslinking agent has a weight average molecular weight of 50 to 200 g / mol, more specifically, a weight average molecular weight of 50 g / mol or more, or 60 g / mol or more, or 70 g / mol or more, or 75 g / mol or more, and 200 g / mol or less, or 150 g / mol or less, or 120 g / mol or less, or 100 g / mol or less, or 90 g / mol or less, or 85 g / mol or less, and the second surface crosslinking agent has a weight average molecular weight of 100 to 600 g / mol, more specifically, a weight average molecular weight of 100 g / mol or more. the amount is 100 g / mol or more, or 120 g / mol or more, or 150 g / mol or more, or 170 g / mol or more, and 500 g / mol or less, or 300 g / mol or less, or 250 g / mol or less, or 220 g / mol or less, and the weight average molecular weights of the first surface crosslinking agent and the second surface crosslinking agent may satisfy that the ratio of the weight average molecular weight of the second surface crosslinking agent to the first surface crosslinking agent is 1.8 or more, or 1.95 or more, or 2 or more, or 2.2 or more, and 15 or less, or 10 or less, or 5 or less, or 3 or less.
[0110] In addition, since the second surface crosslinking reaction using the second surface crosslinking agent is carried out using residual heat during cooling after the completion of the first surface crosslinking reaction, the second surface crosslinking agent is preferably one capable of quickly forming a covalent bond with an acidic group, specifically a carboxyl group, in the crosslinked polymer of the water-soluble ethylenically unsaturated monomer in the reaction temperature range during the second surface crosslinking reaction, specifically 120 to 150°C. For this reason, the second surface crosslinking agent has two or more epoxide functional groups capable of crosslinking with the crosslinked polymer present on the surface of the base resin powder, and an epoxy compound having a boiling point of 150°C or more under normal pressure (normal pressure or atmospheric pressure) conditions, more specifically 1±0.2 atm conditions, can be used. If the boiling point is less than 150°C, the surface crosslinking agent before the reaction may evaporate due to residual heat of the superabsorbent resin, resulting in a decrease in efficiency compared to the amount added. More specifically, the epoxy compound may have a boiling point of 150°C or more, or 180°C or more, or 200°C or more, or 250°C or more, or 260°C or more, or 265°C or more, and may be 500°C or less, or 350°C or less, or 300°C or less, or 280°C or less.
[0111] Specific examples of the second surface cross-linking agent include one or more epoxy compounds such as ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, propylene glycol diglycidyl ether, hexanediol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol diglycidyl ether, and polyethylene glycol diglycidyl ether.
[0112] The polyethylene glycol diglycidyl ether or polypropylene glycol diglycidyl ether may have a weight average molecular weight of 200 to 600 g / mol. The weight average molecular weight (Mw) of the polyethylene glycol diglycidyl ether or polypropylene glycol diglycidyl ether may be measured by gel permeation chromatography. The specific measurement method and conditions are the same as those of the measurement method of the weight average molecular weight (Mw) of polycarboxylic acid described below, except that the Mw value is derived using a calibration curve for a polystyrene standard specimen.
[0113] The second surface crosslinking agent can be used in an amount of 0.001 to 1 part by weight based on 100 parts by weight of the base resin that has been primarily surface crosslinked. If the amount of the second surface crosslinking agent used is less than 0.001 part by weight, the second surface crosslinking is not sufficiently performed, resulting in a small effect of improving the absorbency of the superabsorbent resin, and if the amount exceeds 1 part by weight, excessive surface crosslinking is performed, resulting in various physical properties of the superabsorbent resin, especially the dryness, being deteriorated. More specifically, the second surface crosslinking agent can be used in an amount of 0.001 part by weight or more, or 0.003 part by weight or more, or 0.005 part by weight or more, or 1 part by weight or less, or 0.5 parts by weight or less, or 0.1 parts by weight or less, or 0.05 parts by weight or less, or 0.02 parts by weight or less, or 0.01 parts by weight or less based on 100 parts by weight of the base resin that has been primarily surface crosslinked.
[0114] In addition, during the second surface crosslinking, at least one of polycarboxylic acid or a salt thereof may be selectively added together with the second surface crosslinking agent.
[0115] The polycarboxylic acid and its salt act as a lubricant that helps the second surface crosslinking agent to be evenly applied to the surface of the primarily surface crosslinked base resin powder. In general, the permeability of the physical properties of a superabsorbent resin is in a trade-off relationship with the water retention capacity and the water absorption capacity under pressure, and when the polycarboxylic acid or its salt is added, it is possible to provide a superabsorbent resin that has excellent absorption properties such as the water retention capacity and the water absorption capacity under pressure, as well as improved permeability.
[0116] The polycarboxylic acid or its salt is not particularly limited as long as it is used in the production of a highly water-absorbent resin. It may be directly produced and used. TM Commercially available products such as those manufactured by Aegis Co., Ltd. can also be used.
[0117] Specifically, the polycarboxylic acid or its salt may be a copolymer or its salt containing at least one of a repeating unit represented by the following chemical formula 2-a or a repeating unit represented by the following chemical formula 2-b:
[0118] [ka]
[0119] In the above chemical formulas 2-a and 2-b, R 1 , R 2 and R 3 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, RO is an oxyalkylene group having 2 to 4 carbon atoms; M 1 is hydrogen or a monovalent metal or nonmetal ion, X is -COO-, an alkyloxy group having 1 to 5 carbon atoms, or an alkyldioxy group having 1 to 5 carbon atoms; m is an integer from 1 to 100; n is an integer from 1 to 1000, p is an integer of 1 to 150, and when p is 2 or more, two or more repeated --RO-- may be the same or different.
[0120] Here, the polycarboxylic acid or its salt may be one or more repeating units having structures different from each other among the repeating units represented by chemical formula 2-a; one or more repeating units having structures different from each other among the repeating units represented by chemical formula 2-b; or a copolymer containing the repeating unit represented by chemical formula 2-a and the repeating unit represented by chemical formula 2-b or its salt.
[0121] The salt of the polycarboxylic acid may be at least one selected from the group consisting of monovalent (alkali) metal salts, divalent metal salts, ammonium salts, and organic amine salts of the polycarboxylic acid.
[0122] More specifically, as the polycarboxylic acid or its salt, it may be advantageous to use a random copolymer or its salt containing repeating units derived from hydrophilic monomers such as an alkoxy polyalkylene glycol mono(meth)acrylic acid ester monomer (a representative example is methoxy polyethylene glycol monomethacrylate (MPEGMAA)), and (meth)acrylic acid or its ester monomer (representative examples are (meth)acrylic acid, (meth)acrylate, etc.), in order to exhibit the above-mentioned effects.
[0123] In order to further improve the effect of the addition of the polycarboxylic acid or its salt, the polycarboxylic acid or its salt preferably has a weight average molecular weight of 500 to 1,000,000 g / mol, more specifically, 500 g / mol or more, 5,000 g / mol or more, 10,000 g / mol or more, 35,000 g / mol or more, or 40,000 g / mol or more, and 1,000,000 g / mol or less, 800,000 g / mol or less, or 60,000 g / mol or less. If the molecular weight of the polycarboxylic acid or its salt is less than 500 g / mol, the lubricating effect may be reduced, and if it exceeds 1,000,000 g / mol, the solubility in water may be reduced.
[0124] Meanwhile, in the present invention, the weight average molecular weight (Mw) of polycarboxylic acid or its salt can be measured by gel permeation chromatography. Specifically, a PL-GPC220 instrument manufactured by Waters was used as a gel permeation chromatography (GPC) device, and a PLgel MIX-B column (length 300 mm) manufactured by Polymer Laboratories was used. At this time, the measurement temperature was 160°C, 1,2,4-trichlorobenzene was used as a solvent, and the flow rate was 1 mL / min. 10 mg of a sample of polycarboxylic acid or its salt was pretreated by dissolving it in 1,2,4-trichlorobenzene containing 0.0125% BHT at 160°C for 10 hours using a sample pretreatment system PL-SP260 (manufactured by Agilent Technology), adjusting the concentration to 10 mg / 10 mL, and then supplying it in an amount of 200 μL. The Mw value was derived using a calibration curve formed using a polystyrene standard specimen. Nine types of polystyrene standard specimens with weight average molecular weights of 2,000 g / mol, 10,000 g / mol, 30,000 g / mol, 70,000 g / mol, 200,000 g / mol, 700,000 g / mol, 2,000,000 g / mol, 4,000,000 g / mol, and 10,000,000 g / mol were used.
[0125] The polycarboxylic acid or its salt may be added in an amount of 0.01 parts by weight or more, or 0.03 parts by weight or more, or 0.035 parts by weight or more, and 0.1 parts by weight or less, or 0.08 parts by weight or less, or 0.075 parts by weight or less, or 0.05 parts by weight or less, based on 100 parts by weight of the primarily surface crosslinked base resin.
[0126] In addition, during the second surface crosslinking, an inorganic filler may be selectively added together with the second surface crosslinking agent. The inorganic filler may be included in an amount of 0.01 to 0.5 parts by weight, or 0.1 to 0.5 parts by weight, based on 100 parts by weight of the first surface crosslinked base resin, as described above.
[0127] In addition, during the second surface crosslinking, a thickener may be selectively added together with the second surface crosslinking agent. The thickener is as described above, and may be included in an amount of 0.01 to 0.5 parts by weight, or 0.1 to 0.5 parts by weight based on 100 parts by weight of the first surface crosslinked base resin.
[0128] In addition, there is no limitation on the constitution of the method for mixing the second surface crosslinking agent with the primarily surface crosslinked base resin. For example, the second surface crosslinking agent and the primarily surface crosslinked base resin can be mixed in a reaction vessel, the second surface crosslinking agent can be sprayed onto the base resin, or the base resin and the second surface crosslinking agent can be continuously supplied to a continuously operated mixer and mixed.
[0129] In addition, when the second surface crosslinking agent and the first surface crosslinked base resin are mixed, a solvent such as water or methanol can be further added so that the second surface crosslinking agent is uniformly dispersed in the first surface crosslinked base resin. In addition, by controlling the amount of the solvent to be added, the second surface crosslinking agent can be uniformly dispersed, and the surface crosslinking depth of the second surface crosslinking agent can be optimized while preventing the aggregation phenomenon of the first surface crosslinked base resin. Specifically, the solvent can be used in an amount of 0.5 to 10 parts by weight with respect to 100 parts by weight of the first surface crosslinked base resin.
[0130] On the other hand, the secondary surface cross-linking reaction using the second surface cross-linking agent is carried out at a second temperature, specifically, 120 to 150°C.
[0131] If the second temperature exceeds 150°C, the solvent evaporates quickly before the second surface crosslinking agent is sufficiently mixed with the first surface crosslinked base resin, and is locally absorbed into the first surface crosslinked base resin. As a result, the surface reaction occurs under the condition that the second surface crosslinking agent is locally applied, and the effect of the second surface crosslinking may be reduced. Also, if the second temperature is less than 120°C, the second surface crosslinking reaction does not occur sufficiently, and as a result, the 0.9 AUL drop rate after the anti-caking treatment of the superabsorbent resin may increase significantly. More specifically, the second temperature may be 120°C or more, or 125°C or more, or 130°C or more, and 150°C or less, or 145°C or less, or 140°C or less.
[0132] The secondary surface crosslinking reaction can be carried out under cooling conditions in which the temperature is lowered within the above temperature range.
[0133] In the manufacturing method according to the present invention, after the first surface crosslinking reaction at a high temperature, the second surface crosslinking reaction is carried out using the residual heat after the first surface crosslinking reaction. Thus, the second surface crosslinking reaction can be carried out by maximally using the residual heat after the first surface crosslinking reaction by controlling the timing of adding the second surface crosslinking agent and the cooling conditions. In addition, compared to the case where the second surface crosslinking reaction is carried out while maintaining a constant temperature, the penetration speed of the second surface crosslinking agent into the superabsorbent resin surface can be more easily controlled.
[0134] Specifically, the second surface crosslinking can be performed by adding a second surface crosslinking agent when the temperature of the first surface crosslinked base resin is 140 to 150°C, and lowering the temperature to 120 to 130°C.
[0135] When the second surface crosslinking is performed under the above conditions, the efficiency of the second surface crosslinking reaction can be further increased, and as a result, the physical properties of the superabsorbent resin produced, particularly the 0.9 AUL drop rate after anti-caking treatment of the superabsorbent resin, can be further reduced. If the temperature of the first surface crosslinked base resin powder is less than 140°C when the second surface crosslinking agent is added, it is difficult to maximize the effect of improving the efficiency of the second surface crosslinking reaction. In addition, if the temperature of the first surface crosslinked base resin powder exceeds 150°C when the second surface crosslinking agent is added, the solvent evaporates quickly before the second surface crosslinking agent is sufficiently mixed with the first surface crosslinked base resin, and is locally absorbed into the first surface crosslinked base resin. As a result, the surface reaction is performed under conditions where the second surface crosslinking agent is locally applied, and the effect of the second surface crosslinking may be reduced.
[0136] In addition, by controlling the cooling rate during the secondary surface cross-linking reaction under the above cooling conditions, the efficiency of the surface cross-linking reaction can be increased, and as a result, the physical properties of the superabsorbent resin produced can be further improved.
[0137] Specifically, the second surface crosslinking reaction can be carried out by adding a second surface crosslinking agent when the temperature of the first surface crosslinked base resin powder is 140 to 150° C., and lowering the temperature to 120 to 130° C. at a cooling rate of −1.5 to −2.0° C. / min. In this case, “-” in the cooling rate means that the reaction is carried out while the temperature is being lowered.
[0138] In addition, if the cooling rate during the second surface crosslinking is less than -1.5°C / min, it is difficult to ensure sufficient surface crosslinking strength due to the rapid evaporation of the solvent in the surface crosslinking agent and the resulting low penetration depth of the surface crosslinking agent. Also, if the cooling rate exceeds -2.0°C / min, the reaction rate of the surface crosslinking agent slows down due to the rapid temperature drop, and the reaction does not proceed sufficiently, resulting in a risk of a decrease in surface crosslinking strength.
[0139] In addition, the cooling during the second surface crosslinking reaction may be performed by natural cooling in which the temperature of the reaction system is naturally lowered to room temperature after the completion of the first surface crosslinking reaction, or may be performed by a conventional cooling method such as circulating cold air, cold water, or cooling oil. As an example, the cooling may be performed by putting a reactor or reservoir containing the reaction system into an oil circulating water tank after introducing the second surface crosslinking agent, and circulating low-temperature oil.
[0140] Meanwhile, step 4 may additionally include a process of classifying the second surface cross-linked base resin.
[0141] The properties of the superabsorbent resin powder, which is the final product, can be controlled by classifying the second surface crosslinked base resin according to particle size. It is appropriate that the superabsorbent resin obtained through the processes of crushing and classifying has a particle size of about 150 to 850 μm. More specifically, at least about 95% by weight of the second surface crosslinked base resin has a particle size of about 150 to 850 μm, and fine powder having a particle size of less than about 150 μm can be less than about 3% by weight. By controlling the particle size distribution of the superabsorbent resin to a preferred range, the final superabsorbent resin can exhibit excellent absorption properties. Therefore, in the classification step, a polymer having a particle size of about 150 to about 850 μm can be classified and commercialized.
[0142] The superabsorbent resin produced by the production method of the present invention as described above specifically includes a base resin powder containing a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a part of a neutralized acidic group; and a surface crosslinked layer located on the base resin powder, the surface crosslinked layer including a first crosslinked polymer in which a part of the crosslinked polymer is additionally crosslinked via a first surface crosslinking agent; and a second crosslinked polymer in which the remainder of the crosslinked polymer is additionally crosslinked via a second surface crosslinking agent. At this time, the first and second surface crosslinking agents are as described above.
[0143] More specifically, in the surface cross-linked layer, the first cross-linked polymer is located adjacent to the base resin powder, and the second cross-linked polymer is located outside the superabsorbent resin. As a result, the cross-linking density increases toward the outside of the superabsorbent resin, so that the superabsorbent resin has improved surface strength and can exhibit the effect of reducing the AUL decrease due to the anti-caking treatment.
[0144] Specifically, the superabsorbent polymer has a centrifugation retention capacity (CRC) of 30 g / g or more, more specifically 32 g / g or more, in physiological saline (0.9 wt % sodium chloride aqueous solution) for 30 minutes, as measured by EDANA method 442.0-96. The higher the CRC, the better, and there is no substantial upper limit, but it may be, for example, 50 g / g or less, or 40 g / g or less.
[0145] In addition, the superabsorbent polymer has a 0.9 AUL drop rate of 0.05 or less, more specifically 0.03 or less, calculated by the following Equation 1. The smaller the 0.9 AUL drop rate, the better, and there is no substantial lower limit, but for example, it may be 0.001 or more, 0.01 or more, or 0.02 or more.
[0146] [Formula 1] 0.9AUL decline rate=[(AB) / A]
[0147] (In the above formula 1, A is 0.9 AUL of the superabsorbent polymer before the anti-caking treatment, and is the water absorption capacity under pressure measured after swelling the superabsorbent polymer before the anti-caking treatment under a pressure of 0.9 psi for 1 hour according to the EDANA method 442.0-96; B is 0.9 AUL of the anti-caking treated superabsorbent resin, which is the water absorption capacity under pressure measured after the anti-caking treatment is performed by dry mixing 100 parts by weight of the superabsorbent resin and 0.0005 to 0.001 parts by weight, more specifically 0.001 parts by weight of fumed silica as an anti-caking agent, at 200 rpm for 30 seconds to 1 minute, more specifically 1 minute, and then swelling the anti-caking treated superabsorbent resin under a pressure of 0.9 psi for 1 hour according to the EDANA method 442.0-96.
[0148] Specifically, the superabsorbent resin may have a 0.9 AUL of 15 to 30 before the anti-caking treatment, and a 0.9 AUL of 15 to 25 after the anti-caking treatment.
[0149] Specifically, the superabsorbent resin may have a 0.9 AUL of 15 to 30, or 18 to 23 before the anti-caking treatment, and a 0.9 AUL of 15 to 25, or 17 to 22 after the anti-caking treatment.
[0150] Therefore, the superabsorbent polymer can be very suitably applied to various sanitary products such as adult diapers, and can be effectively used in sanitary products having a reduced pulp content. The sanitary products include disposable absorbent products, and preferably include diapers, which may be either baby or adult diapers. Effect of the Invention
[0151] According to the production method of the present invention, it is possible to produce a superabsorbent resin which exhibits little or no decrease in water absorption capacity under pressure even after anti-caking treatment by increasing the surface crosslinking strength of the superabsorbent resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0152] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these examples are presented only as examples of the present invention and do not determine the scope of the invention. EXAMPLES
[0153] <Production of base resin> Manufacturing Example A monomer composition was prepared by mixing 100 parts by weight of acrylic acid, 126.8 parts by weight of 31.5% caustic soda (NaOH), 46 parts by weight of water, and the following components.
[0154] - Internal crosslinking agent: polyethylene glycol diacrylate (PEGDA; Mw=400) 0.2 parts by weight (2000 ppmw) -Polymerization initiator: 0.008 parts by weight (80 ppmw) of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (photopolymerization initiator) and 0.12 parts by weight (1200 ppmw) of sodium persulfate (thermal polymerization initiator)
[0155] The composition was fed into a feed section of a polymerization vessel consisting of a continuously moving conveyor belt, and irradiated with ultraviolet light for 1.5 minutes (approximately 2 mW / cm ) using a UV irradiation device. 2 ) A polymerization reaction was carried out to obtain a hydrogel polymer as the product.
[0156] The hydrogel polymer was cut using a cutter. Then, the hydrogel polymer was dried in a hot air dryer at 190°C for 40 minutes, and the dried hydrogel polymer was pulverized using a pulverizer. Then, the polymer particles having a particle size of 150 to 850 μm were classified using a sieve to obtain a base resin powder.
[0157] The resulting base resin powder had a CRC value of about 54 g / g.
[0158] <Production of superabsorbent resin> Example 1 Based on 100 parts by weight of the base resin powder prepared in the above Preparation Example, 4 parts by weight of water, 3 parts by weight of methanol, 1.5 parts by weight of ethylene carbonate (weight average molecular weight = 88.06 g / mol) as a first surface crosslinking agent, and 0.05 parts by weight of fumed silica were mixed in a ratio to prepare a first surface crosslinking liquid.
[0159] The first surface crosslinking liquid was added to 100 parts by weight of the base resin powder prepared in the above Preparation Example, and the mixture was thoroughly mixed by stirring at a speed of about 200 rpm for less than 10 seconds using a high-speed mixer. The resulting mixture was placed in a reactor and heated to about 180°C for about 20 minutes, and then reacted for 30 minutes while maintaining the elevated temperature to perform the first surface crosslinking (first surface crosslinking, total reaction time 50 minutes).
[0160] After the completion of the first surface crosslinking, when the temperature of the reaction system was lowered to 150°C, 3 parts by weight of water, 0.02 parts by weight of ethylene glycol diglycidyl ether (weight average molecular weight = 174.19 g / mol, boiling point: 266.8°C (at 1 atm)) as a second surface crosslinking agent, and 50% by weight of polycarboxylic acid aqueous solution (ACYMA-GK TM A secondary surface crosslinking liquid prepared by mixing 0.1 parts by weight of 1,2-dichlorophenyl ether (manufactured by Aegis Co., Ltd.) was added, and the mixture was thoroughly mixed by stirring at a speed of about 200 rpm for less than 10 seconds using a high-speed mixer.
[0161] The resulting mixture was placed in a stirrer and stirred without additional heating to carry out secondary surface crosslinking. At this time, the reservoir containing the mixture during the stirring process was placed in an oil circulating water bath to circulate the oil and lower the temperature, thereby lowering the reaction temperature from 150°C to 120°C at a cooling rate of -1.5°C / min (secondary surface crosslinking, total reaction time: 20 min).
[0162] After the surface cross-linking was completed, the resulting resin powder was put into a grinder, pulverized, and classified using a sieve to obtain a highly water-absorbent resin having a particle size of 150 to 850 μm.
[0163] Example 2 Based on 100 parts by weight of the base resin powder prepared in the above Preparation Example, 3 parts by weight of water, 3.5 parts by weight of methanol, 1 part by weight of ethylene carbonate (weight average molecular weight = 88.06 g / mol) as a first surface crosslinking agent, and 0.03 parts by weight of fumed silica were mixed in a ratio to prepare a first surface crosslinking liquid.
[0164] The first surface crosslinking liquid was added to 100 parts by weight of the base resin powder prepared in the above Preparation Example, and the mixture was thoroughly mixed by stirring at a speed of about 200 rpm for less than 10 seconds using a high-speed mixer. The resulting mixture was placed in a reactor and heated to about 180°C for about 20 minutes, and then reacted for 30 minutes while maintaining the elevated temperature to perform the first surface crosslinking (first surface crosslinking, total reaction time 50 minutes).
[0165] Thereafter, when the temperature of the reaction system was lowered to 150°C, 100 parts by weight of the base resin that had been subjected to the first surface crosslinking were mixed with 3 parts by weight of water, 0.005 parts by weight of 1,4-butanediol diglycidyl ether (weight average molecular weight = 202.25 g / mol, boiling point: 266°C) as an epoxy-based second surface crosslinking agent, and a 50% by weight concentration aqueous solution of polycarboxylic acid (ACYMA-GK TM A secondary surface crosslinking liquid prepared by mixing 0.07 parts by weight of 1,2-dichlorophenyl ether (manufactured by Aegis Co., Ltd.) was added, and the mixture was thoroughly mixed while stirring using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds.
[0166] The resulting mixture was placed in a stirrer and stirred without additional heating to perform secondary surface crosslinking. At this time, the reservoir containing the mixture during the stirring process was placed in an oil circulating water bath to circulate the oil while lowering the temperature, thereby lowering the reaction temperature from 150°C to 120°C at a cooling rate of -1.5°C / min (secondary surface crosslinking, total reaction time: 20 min).
[0167] After the surface cross-linking was completed, the resulting resin powder was put into a grinder, pulverized, and classified using a sieve to obtain a highly water-absorbent resin having a particle size of 150 to 850 μm.
[0168] Example 3 Based on 100 parts by weight of the base resin powder prepared in the above Preparation Example, 4 parts by weight of water, 3.5 parts by weight of methanol, 0.2 parts by weight of 1,3-propanediol (weight average molecular weight = 79.09 g / mol) as a first surface crosslinking agent, 0.15 parts by weight of oxalic acid, and 0.01 parts by weight of fumed silica were mixed in a ratio to prepare a first surface crosslinking liquid.
[0169] The first surface crosslinking liquid was added to 100 parts by weight of the base resin powder prepared in the above Preparation Example, and mixed thoroughly using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds. The resulting mixture was placed in a reactor and heated to about 190°C for about 20 minutes, and then reacted for 20 minutes while maintaining the elevated temperature to perform the first surface crosslinking (first surface crosslinking, total reaction time 40 minutes).
[0170] Thereafter, when the temperature of the reaction system was lowered to 150° C., 100 parts by weight of the base resin that had been subjected to the first surface crosslinking were mixed with 3 parts by weight of water, 0.005 parts by weight of ethylene glycol diglycidyl ether (weight average molecular weight=174.19 g / mol, boiling point: 266.8° C. (at 1 atm)) as a second surface crosslinking agent, and 50% by weight of an aqueous solution of polycarboxylic acid (ACYMA-GK TM A secondary surface crosslinking liquid prepared by mixing 0.15 parts by weight of 1,2-dichlorophenyl ether (manufactured by Aegis Co., Ltd.) was added, and the mixture was thoroughly mixed while stirring using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds.
[0171] The resulting mixture was placed in a stirrer and stirred without additional heating to carry out secondary surface crosslinking. During this process, the reservoir containing the mixture was placed in an oil circulating water bath to circulate the oil and lower the temperature, thereby lowering the reaction temperature from 150°C to 130°C at a cooling rate of -2.0°C / min (secondary surface crosslinking, total reaction time: 10 min).
[0172] After the surface cross-linking was completed, the resulting resin powder was put into a grinder, pulverized, and classified using a sieve to obtain a highly water-absorbent resin having a particle size of 150 to 850 μm.
[0173] Example 4 Based on 100 parts by weight of the base resin powder prepared in the above Preparation Example, 4 parts by weight of water, 3.5 parts by weight of methanol, 0.4 parts by weight of 1,3-propanediol (weight average molecular weight = 79.09 g / mol) as a first surface crosslinking agent, 0.23 parts by weight of oxalic acid, and 0.04 parts by weight of fumed silica were mixed in a ratio to prepare a first surface crosslinking liquid.
[0174] The first surface crosslinking liquid was added to 100 parts by weight of the base resin powder prepared in the above Preparation Example, and mixed thoroughly using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds. The resulting mixture was placed in a reactor and heated to about 185°C for about 20 minutes, and then reacted for 25 minutes while maintaining the elevated temperature to perform the first surface crosslinking (first surface crosslinking, total reaction time 45 minutes).
[0175] Thereafter, when the temperature of the reaction system was lowered to 140° C., 100 parts by weight of the base resin that had been subjected to the first surface crosslinking were mixed with 3 parts by weight of water, 0.01 parts by weight of ethylene glycol diglycidyl ether (weight average molecular weight=174.19 g / mol, boiling point: 266.8° C. (at 1 atm)) as a second surface crosslinking agent, and 50% by weight of an aqueous polycarboxylic acid solution (ACYMA-GK TM A secondary surface crosslinking liquid prepared by mixing 0.15 parts by weight of 1,2-dichlorophenyl ether (manufactured by Aegis Co., Ltd.) was added, and the mixture was thoroughly mixed while stirring using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds.
[0176] The resulting mixture was placed in a stirrer and stirred without additional heating to carry out secondary surface crosslinking. At this time, the reservoir containing the mixture during the stirring process was placed in an oil circulating water bath to circulate the oil and lower the temperature, thereby lowering the reaction temperature from 140°C to 120°C at a cooling rate of -1.5°C / min (secondary surface crosslinking, total reaction time: about 13 minutes).
[0177] After the surface cross-linking was completed, the resulting resin powder was put into a grinder, pulverized, and classified using a sieve to obtain a highly water-absorbent resin having a particle size of 150 to 850 μm.
[0178] Comparative Example 1 A highly water-absorbent resin was prepared in the same manner as in Example 1, except that only the first surface cross-linking was carried out.
[0179] Comparative Example 2 A highly water-absorbent resin was prepared in the same manner as in Example 2, except that only the first surface cross-linking was carried out.
[0180] Comparative Example 3 A superabsorbent resin was prepared in the same manner as in Comparative Example 1, except that the content of ethylene carbonate in the first surface cross-linking solution was increased to 1.8 parts by weight.
[0181] Comparative Example 4 Based on 100 parts by weight of the base resin powder produced in the above Production Example, 3 parts by weight of water, 0.02 parts by weight of ethylene glycol diglycidyl ether (weight average molecular weight = 174.19 g / mol, boiling point: 266.8 ° C (at 1 atm)) as an epoxy surface crosslinking agent, and 50% by weight of polycarboxylic acid aqueous solution (ACYMA-GK TM A primary surface cross-linking liquid was prepared by mixing 0.1 parts by weight of 1,2-dichlorophenyl ether (manufactured by Aegis Co., Ltd.).
[0182] The first surface crosslinking liquid was added to 100 parts by weight of the base resin powder prepared in the above Preparation Example, and mixed thoroughly using a high-speed mixer at a speed of about 200 rpm for less than 10 seconds. The resulting mixture was placed in a reactor and reacted at about 130°C for 20 minutes to perform the first surface crosslinking (first surface crosslinking, total reaction time: 20 minutes).
[0183] A secondary surface crosslinking liquid was prepared by mixing 4 parts by weight of water, 3 parts by weight of methanol, 1.5 parts by weight of ethylene carbonate (weight average molecular weight = 88.06 g / mol), and 0.05 parts by weight of fumed silica with respect to 100 parts by weight of the primarily surface crosslinked base resin, and the mixture was thoroughly mixed while stirring at a speed of about 200 rpm for less than 10 seconds using a high-speed mixer.
[0184] The resulting mixture was placed in a reactor and heated to about 180° C. for about 20 minutes, and then reacted for 30 minutes while maintaining the elevated temperature to perform secondary surface crosslinking (secondary surface crosslinking, total reaction time 50 minutes).
[0185] After the surface cross-linking was completed, the obtained resin powder was put into a crusher and crushed, and then classified using a sieve to obtain a highly water-absorbent resin having a particle size of 150 to 850 μm.
[0186] Comparative Example 5 A superabsorbent resin was produced in the same manner as in Example 1, except that the second surface cross-linking liquid was added when the temperature of the reaction system was lowered to 110°C after the completion of the first surface cross-linking, and the reaction temperature for the second surface cross-linking was lowered from 110°C to 80°C at a cooling rate of -1.5°C / min.
[0187] Comparative Example 6 A superabsorbent resin was prepared in the same manner as in Example 1, except that in preparing the second surface crosslinking solution of Example 1, 1,3-butadiene diepoxide (weight average molecular weight: 86.01 g / mol) was used as an epoxy-based second surface crosslinking agent instead of ethylene glycol diglycidyl ether.
[0188] Comparative Example 7 After the first surface crosslinking in Example 2, a superabsorbent resin was produced in the same manner as in Example 2, except that a second surface crosslinking liquid was added, which was prepared by mixing 3 parts by weight of water, 0.03 parts by weight of PEG600 (boiling point 200°C (at 1 atm)) and 0.1 parts by weight of a 50% polycarboxylic acid aqueous solution with respect to 100 parts by weight of the first surface crosslinked base resin, and a second surface crosslinking reaction was carried out at a temperature of 180°C for a total reaction time of 50 minutes.
[0189] Comparative Example 8 A superabsorbent resin was prepared in the same manner as in Example 1, except that in preparing the second surface crosslinking solution of Example 1, 0.05 parts by weight of aluminum sulfate (Mw: 342.15 g / mol) was used instead of ethylene glycol diglycidyl ether as an epoxy-based second surface crosslinking agent.
[0190] Experimental Example The superabsorbent resins obtained in the above Examples and Comparative Examples were measured for various absorption-related physical properties by the following methods.
[0191] (1)Centrifuge Retention Capacity (CRC) Centrifuge retention capacity (CRC) was measured by the EDANA method WSP 241.3.
[0192] Specifically, among the superabsorbent resins to be measured for centrifugal water retention capacity, a superabsorbent resin with a particle size of 300-600 μm that passes through a US standard 30 mesh screen and is retained on a US standard 50 mesh screen was prepared. Then, the superabsorbent resin with a particle size of 300-600 μm W0 (g, about 0.2 g) was uniformly placed in a nonwoven fabric envelope and sealed. Then, the envelope was immersed in 0.9 wt % physiological saline at room temperature. After 30 minutes, the envelope was dehydrated at 250 G for 3 minutes using a centrifuge, and the weight of the envelope W4 (g) was measured. Meanwhile, the same operation was performed using an empty envelope without the superabsorbent resin, and the weight at that time W3 (g) was measured.
[0193] Using the weights thus obtained, the centrifugal water retention capacity was determined according to the following formula 2.
[0194] [Formula 2] CRC(g / g)={[W4(g)-W3(g)] / W0(g)}-1
[0195] In the above formula 2, W0 (g) is the initial weight (g) of the superabsorbent resin having a particle size of 300 μm to 600 μm, W3 (g) is the weight of the device measured after dehydrating the device at 250 G for 3 minutes using a centrifuge without using a superabsorbent resin. W4(g) is the weight of the device including the superabsorbent polymer after immersing and absorbing the superabsorbent polymer having a particle size of 300 μm to 600 μm in 0.9 wt % physiological saline at room temperature for 30 minutes, and then spinning the superabsorbent polymer at 250 G for 3 minutes using a centrifuge.
[0196] (2) Absorbency under Load (AUL) The 0.9 AUL of the superabsorbent resins prepared in the above Examples and Comparative Examples was measured before and after the anti-caking treatment, and the rate of decrease in absorbency under pressure after the anti-caking treatment was calculated from the results.
[0197] Specifically, the anti-caking treatment for the superabsorbent resin was carried out by placing 100 parts by weight of the superabsorbent resin and 0.001 parts by weight of fumed silica (Aerosil (registered trademark) 200 by Evonik) as an anti-caking agent in a 500 ml polyethylene (PE) bottle, and dry mixing the PE bottle for 30 seconds at 200 rpm using a vortex mixer (MS3 by IKA).
[0198] The absorbency under pressure (AUL) of the superabsorbent resin before and after the anti-caking treatment for physiological saline at 0.9 psi was measured by the EDANA method 442.0-96.
[0199] Specifically, a stainless steel 400 mesh screen was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. Then, the superabsorbent resin W0 (g, about 0.16 g) whose pressurized water absorption capacity was to be measured was uniformly spread on the screen at room temperature and 50% humidity. Then, a piston capable of uniformly applying a load of 6.3 kPa (0.9 psi) was added onto the superabsorbent resin. At this time, the piston used had an outer diameter slightly smaller than 25 mm, no gap with the inner wall of the cylinder, and was manufactured so that it could move up and down freely. Then, the weight W5 (g) of the device thus prepared was measured. Next, a glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and 0.9 wt % physiological saline was poured into the Petri dish. At this time, the physiological saline was poured until the water level of the physiological saline was level with the top surface of the glass filter. Then, a sheet of filter paper with a diameter of 90 mm was placed on the glass filter. Next, the prepared device was placed on the filter paper so that the superabsorbent polymer in the device was swollen by the physiological saline under the load. After one hour, the weight W6 (g) of the device containing the swollen superabsorbent polymer was measured.
[0200] Using the weight thus measured, the water absorption capacity under pressure was calculated according to the following Equation 3.
[0201] [Formula 3] AUL(g / g)=[W6(g)-W5(g)] / W0(g)
[0202] In the above formula 3, W0 (g) is the initial weight of the superabsorbent polymer (g), W5(g) is the total weight of the superabsorbent polymer and the weight of a device capable of applying a load to the superabsorbent polymer, W6(g) is the total weight of the superabsorbent polymer and the weight of a device capable of applying a load to the superabsorbent polymer after the superabsorbent polymer is allowed to absorb saline solution under a load (0.9 psi) for 1 hour.
[0203] Using the 0.9 AUL values measured before and after the anti-caking treatment, the 0.9 AUL drop rate was calculated according to the following Equation 1:
[0204] [Formula 1] 0.9AUL decline rate=[(AB) / A]
[0205] (In the above formula 1, A is 0.9 AUL of the superabsorbent polymer before the anti-caking treatment, and is the water absorption capacity under pressure measured after swelling the superabsorbent polymer before the anti-caking treatment under a pressure of 0.9 psi for 1 hour according to EDANA method 442.0-96; B is 0.9 AUL of the anti-caking treated superabsorbent resin, which is measured after anti-caking treatment by dry mixing 100 parts by weight of the superabsorbent resin and 0.0005 to 0.001 parts by weight of fumed silica as an anti-caking agent at 200 rpm for 30 seconds to 1 minute, and then swelling the anti-caking treated superabsorbent resin under a pressure of 0.9 psi for 1 hour according to the EDANA method 442.0-96.
[0206] The measurement results are shown in Table 1 below.
[0207] [Table 1]
[0208] As a result of the experiment, the superabsorbent resins of Examples 1 to 4 exhibited superior CRC compared to the Comparative Example, and the 0.9 AUL drop rate was significantly reduced even after the anti-caking treatment.
[0209] On the other hand, in the case of Comparative Examples 1 and 2 in which only the first surface crosslinking was performed, the 0.9 AUL drop rate after the anti-caking treatment was large at 0.15 or more, and in the case of Comparative Example 3 in which only the first surface crosslinking was performed but the content of the surface crosslinking agent was increased, the 0.9 AUL drop rate decreased compared to Comparative Examples 1 and 2, but showed a significantly increased 0.9 AUL drop rate compared to the Examples.
[0210] In addition, in the case of Comparative Example 4, which does not satisfy the conditions for the first and second surface crosslinking of the present invention, a 0.9 AUL drop rate was shown, which is larger than that of Comparative Examples 1 to 3, in which only the first surface crosslinking was performed. In Comparative Example 4, despite the second surface crosslinking, the surface crosslinking agent was not able to penetrate deep into the surface of the superabsorbent resin because a surface crosslinking agent with a large weight average molecular weight was used in the first surface crosslinking, and the strength of the surface crosslinking was not sufficiently secured compared to the examples and Comparative Examples 1 to 3 because the second surface crosslinking was performed using a surface crosslinking agent with a small weight average molecular weight.
[0211] In addition, in the case of Comparative Example 5 in which the temperature condition during the second surface crosslinking was excessively low, the second surface crosslinking reaction was not sufficiently performed, and therefore the 0.9 AUL drop rate after the anti-caking treatment was large. In addition, in the case of Comparative Example 6 in which the weight average molecular weight conditions of the first surface crosslinking agent and the second surface crosslinking agent were not satisfied, the 0.9 AUL drop rate after the anti-caking treatment was reduced compared to other Comparative Examples, but the 0.9 AUL drop rate after the anti-caking treatment was large compared to the Examples, and the CRC properties were also reduced.
[0212] In addition, in the case of Comparative Example 7 in which PEG600, which forms a covalent bond at a temperature range exceeding 150° C., was used as the second surface cross-linking agent, the drop rate of 0.9 AUL after the anti-caking treatment was also large.
[0213] In addition, in the case of Comparative Example 8 in which aluminum sulfate was used as the second surface crosslinking agent, the 0.9 AUL drop rate was reduced compared to Comparative Example 1, but when compared to Example 1 in which only the second surface crosslinking agent was different under the same conditions, the 0.9 AUL drop rate after the anti-caking treatment was large because sufficient surface crosslinking strength was not secured.
Claims
1. a step of cross-linking polymerizing a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of a polymerization initiator and an internal cross-linking agent to form a hydrogel polymer comprising a cross-linked polymer of the water-soluble ethylenically unsaturated monomer; drying, grinding, and classifying the hydrogel polymer to obtain a base resin powder; A step of primarily surface-crosslinking the base resin powder while increasing the temperature to a first temperature in the presence of a first surface-crosslinking agent; and a step of secondarily surface-crosslinking the primarily surface-crosslinked base resin powder at a second temperature in the presence of a second surface-crosslinking agent to form highly absorbent resin particles; The first temperature is 180° C. or more, and the second temperature is 120° C. to 150° C.; the second surface cross-linking agent has a weight average molecular weight larger than that of the first surface cross-linking agent and contains an epoxy-based compound capable of forming a covalent bond at the second temperature; A method for producing a superabsorbent resin.
2. 2. The method for producing a highly water-absorbent resin according to claim 1, wherein a ratio of a weight average molecular weight of the second surface crosslinking agent to that of the first surface crosslinking agent is 1.8 or more.
3. The method for producing a highly water-absorbent resin according to claim 1 or 2, wherein the first surface cross-linking agent comprises one or more compounds selected from the group consisting of polyhydric alcohols and alkylene carbonates.
4. The first surface crosslinking agent is selected from the group consisting of ethylene carbonate, propylene carbonate, ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol. The method for producing a superabsorbent resin according to any one of claims 1 to 3, comprising at least one selected from the group consisting of ethylene carbonate, propylene carbonate, ethylene glycol, propylene ...
5. The method for producing a superabsorbent resin according to claim 1 , wherein at least one of an inorganic filler and an organic acid is further added during the primary surface crosslinking.
6. The method for producing a superabsorbent resin according to claim 5, wherein the inorganic filler comprises at least one selected from the group consisting of silica, fumed silica, clay, alumina, silica-alumina composites, titania, zinc oxide, and silicate.
7. 6. The method for producing a highly absorbent resin according to claim 5, wherein the organic acid comprises at least one selected from the group consisting of oxalic acid, acetic acid, lactic acid, citric acid, fumaric acid, tartaric acid, and maleic acid.
8. The method for producing a highly water-absorbent resin according to any one of claims 1 to 7, wherein the second surface crosslinking agent contains an epoxy compound having two or more epoxide functional groups in a molecule and a boiling point of 150°C or higher under normal pressure conditions.
9. The second surface cross-linking agent comprises one or more epoxy compounds selected from the group consisting of ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, propylene glycol diglycidyl ether, hexanediol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol diglycidyl ether, and polyethylene glycol diglycidyl ether. The method for producing a superabsorbent resin according to any one of claims 1 to 8.
10. The method for producing a superabsorbent resin according to claim 1 , wherein a polycarboxylic acid or a salt thereof is further added during the second surface crosslinking.
11. The primary surface crosslinking further includes a primary maintaining step of maintaining the first temperature after increasing the temperature to the first temperature, The method for producing a superabsorbent resin according to claim 1 , wherein the first maintaining step is performed for 50% or more of the total time during which the first surface crosslinking is performed.
12. The method for producing a superabsorbent resin according to any one of claims 1 to 11, wherein the first temperature is 180 to 200°C.
13. The method for producing a highly water-absorbent resin according to any one of claims 1 to 12, wherein, during the secondary surface crosslinking, a second surface crosslinking agent is added when the temperature of the primarily surface-crosslinked base resin powder is 140 to 150°C, and the powder is cooled to a temperature of 120 to 130°C at a cooling rate of -1.5 to -2.0°C / min to perform secondary surface crosslinking.
Citation Information
Patent Citations
Method of making novel recombined DNA
JP1980058096A
Water-absorbing agent and its production
JP1998265582A
Method of manufacturing polyacrylic acid (SALT)-based water-absorbing resin powder
JP2015120933A
Method for producing aqueous liquid absorbent resin particles, and absorbent body and absorbent article
WO2016143739A1
Super absorbent polymer and method for preparing same
WO2020111421A1